IMPACT OF COVID-19 ON SPORTS: A STUDY ABOUT PHYSICAL ACTIVITIES IN EDUCATION AMONG YOUNGSTERS - Sumbal Kaynat; Maria Khan; Rabia Riasat; Muhammad Tariq Khan; Matiullah; Irfan Ullah Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Purpose: The impact of physical inactivity mayvery likely be seen in many areas such as health and social care and the mental well-being of people all across the globe.COVID-19 also affects physical activity and well-being. Problem: The global COVID19 outbreak has resulted in the closure of gyms, stadiums, swimming pools, dance and fitness studios, physical therapy centres, parks, and playgrounds, leaving many people unable to actively participate in their individual or group sports or outdoor physical activities. The WHO recommends 150 minutes of moderate-intensity or 75 minutes of vigorous-intensity physicalactivity per week. Implications: The benefits of such periodic exercise are proven very helpful, especially in times of anxiety, crisis, and fear. There are concerns therefore in the context of the pandemic, lack of access to regular sporting or exercise routines may result in challenges to the immune system, physical health, including by leading to the commencement of or exacerbating existing diseases that have their roots in a sedentary lifestyle. Recommendations: During the COVID-19 pandemic it is even more important for all people to be physically active. Even if it is only a short break, sitting at your desk and doing some walking or stretching. Conclusion: It is concluded that the Covid-19 outbreak has made a significant impact on the mental health, education, physical activates and daily routine of students.